Survei Tentang Manajemen Fisioterapi pada Pasien Pasca Bedah Torak dan Abdomen atas di Rumah Sakit Tipe A dan B di Jawa dan Bali (Fisioterapi : Jurnal Ilmiah Fisioterapi, 2007)
The happening of complication paru pasca operation often found in patients after done operation action in abdomen part on and piston operation. physiotherapy as one of has character to minimalizing risk the happening of complication lung. Technics physio-therapy that used in patient pasca operation highly varied and still to be controversy about technics best to overcome that troubleshoot pasca surgery action. Aim from this watchfulness detects description about physiotherapy management in patient pasca ope-ration action abdomen part on and piston operation in this time done at home ill type a and b at java and balinese. Watchfulness method: a questioner sent to 35 hospital widespread at Java and Balinese that ask about about reference pattern, patient profile, technics physiotherapy that given in patient pasca operation abdomen part on and piston operation. As much as 68,5% from respondent gives response towards this watchfulness. DataÂ  analyzed to use independent t-test and chi-square. Result from this watchfulness is identificated that fisioterapis doesn't has direct access in patient without get reference from doctor. Although in the case of physiotherapy technics kind that is given, fisioterapis only get a little information from doctor. Assumpted that a large part fisioterapis in ope-rated base in erudition that obtained during follow education from in base in scientific. More than 50%respondent doesn't has access towards watchfulness result. Technics breath practice in (deep breating exercise) be technics most commonly used to increase lung function.Keywords: Poet Operative, Thorax and Abdomen, PT Management